Implementation of Selective Harmonics Elimination for Single Phase Inverter using Arduino and Simulink MATLAB model - Taha A. Hussein; Ibrahim I. Sheet (Tikrit Journal of Engineering Sciences, 2020)
This paper presents Arduino controller implementation and Simulink model in MATLAB to eliminate a selected number of harmonics in a single phase inverter. A MATLAB code is written to solve the nonlinear trigonometric that arises in the Fourier analysis of the output of the inverter. Newton’s Raphson method is adopted to find the triggering angles for the four electronic switches in the inverter. All possible combinations of these triggering instants are then computed for period of one cycle. To validate the model a practical set using Arduino controller is implemented. Frequency spectrums of the output of the inverter for both the Simulink model and the practical set are shown for the elimination of certain selected harmonics. Any other selected harmonics can be eliminated using the proposed model.